1982
DOI: 10.1159/000250128
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis of the Lips: The Unusual Köbner Phenomenon Caused by Protruding Upper Teeth

Abstract: Psoriasis of the lips was observed in a 54-year-old female who had suffered from psoriasis vulgaris for 18 years. The psoriasis of the lips was preceded by protrusion of the upper teeth. Topical corticosteroid and later 5-fluorouracil treatment were ineffective. The disease recurred even after replacement of the vermilion by plain mucosa. The disease was successfully treated by replacement of the protruding teeth by a nonirritating prosthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 2 publications
0
10
0
1
Order By: Relevance
“…Lip psoriasis may follow cheilitis or minimal trauma in patients with the genetic predisposition. Brenner et al [24] reported on the induction of lip psoriasis by koebnerization in a patient whose psoriatic condition was triggered by chronic trauma from protruding maxillary dentition. Despite chronicity, the overlapping signs and symptoms, as well as the atypical site of involvement, may cause lip psoriasis to be mistaken for solar cheilosis, chronic eczema, actinic dermatitis, chronic candidiasis or leukoplakia and lead to delayed diagnosis [22].…”
Section: Perioral and Oral Manifestations Of Psoriasismentioning
confidence: 99%
“…Lip psoriasis may follow cheilitis or minimal trauma in patients with the genetic predisposition. Brenner et al [24] reported on the induction of lip psoriasis by koebnerization in a patient whose psoriatic condition was triggered by chronic trauma from protruding maxillary dentition. Despite chronicity, the overlapping signs and symptoms, as well as the atypical site of involvement, may cause lip psoriasis to be mistaken for solar cheilosis, chronic eczema, actinic dermatitis, chronic candidiasis or leukoplakia and lead to delayed diagnosis [22].…”
Section: Perioral and Oral Manifestations Of Psoriasismentioning
confidence: 99%
“…Mild trauma, chronic irritation or protruding teeth can lead to psoriatic lesions on the lips, especially in a genetically predisposed individual [3]. Brenner et al [7] reported a case of psoriatic cheilitis triggered by protruding teeth, the condition was resolved by replacing the teeth with a non-irritating prosthesis. Lip psoriasis is worsened by cold or dry weather, physical manipulation such as lip biting and exuberant rubbing, and by irritating substances, suggesting the Koebner phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis der Lippen kann bei Patienten mit entsprechender genetischer Prä-disposition nach einer Cheilitis oder einem minimalen Trauma auftreten. Brenner et al [24] berichteten über das Auftreten von Lippen-Psoriasis im Rahmen eines Köbner-Phänomens bei einer Patientin, bei der chronische Traumatisierung durch maxilläre Gebissprotrusion der Auslöser für die Psoriasis-Erkrankung war. Ungeachtet der Chronizität können die geteilten Zeichen und Symptome sowie die atypische Lokalisation dazu führen, dass Psoriasis der Lippe mit aktinischer Cheilitis, chronischem Ekzem, aktinischer Dermatitis, chronischer Candidiasis oder Leukoplakie verwechselt und die Diagnosestellung hierdurch verzö-gert wird [22].…”
Section: Periorale Und Orale Manifestationen Der Psoriasisunclassified